2022
DOI: 10.3389/fendo.2022.911526
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics and Gene Mutations of Maturity-Onset Diabetes of the Young Type 5 in Sixty-One Patients

Abstract: AimsMaturity-onset diabetes of the young type 5 (MODY5), a rare disease, is very easy to be misdiagnosed as type 2 diabetes. To get better understanding of the disease, we analyzed the clinical characteristics and gene mutations of MODY5.MethodsPubMed, Cochrane, the China National Knowledge Infrastructure, and Wanfang were searched with the following search terms: “MODY5” OR “HNF1B maturity-onset diabetes of the young” OR “maturity-onset diabetes of the young type 5” OR “renal cysts and diabetes syndrome”. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…In our cohort, both hyperuricemia and hypomagnesemia were found in two of seven patients. Still, it is unclear whether hyperuricemia is an initial feature of HNF1B-related chronic kidney disease or an independent feature [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, both hyperuricemia and hypomagnesemia were found in two of seven patients. Still, it is unclear whether hyperuricemia is an initial feature of HNF1B-related chronic kidney disease or an independent feature [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Dubois-Laforgue et al reported a high prevalence of stages III and IV of CKD (44%) and even ESKD (21%) [12]. Interestingly, patients with 17q12 deletion appear to have CKD stage III-IV and ESKD less often at diagnosis and a significantly better renal function in the follow-up than patients with different pathogenic variants, suggesting a genotype/phenotype correlation [24]. Arterial hypertension, proteinuria, age at the time of diagnosis of diabetes, and the presence of microvascular complications (retinopathy and neuropathy) are also factors correlated with CKD progression.…”
Section: Clinical Spectrummentioning
confidence: 99%